Comparison of Data Normalization Strategies for Array-Based MicroRNA Profiling Experiments and Identification and Validation of Circulating MicroRNAs as Endogenous Controls in Hypertension - Chekka, Lakshmi Manasa S.; Langaee, Taimour; Johnson, Julie A. (Frontiers in Genetics, 2022)
MicroRNAs are small non-coding RNAs with potential regulatory roles in hypertension and drug response. The presence of many of these RNAs in biofluids has spurred investigation into their role as possible biomarkers for use in precision approaches to healthcare. One of the major challenges in clinical translation of circulating miRNA biomarkers is the limited replication across studies due to lack of standards for data normalization techniques for array-based approaches and a lack of consensus on endogenous control normalizers for qPCR-based candidate miRNA profiling studies. We conducted genome-wide profiling of 754 miRNAs in baseline plasma of 36 European American individuals with uncomplicated hypertension selected from the PEAR clinical trial, who had been untreated for hypertension for at least one month prior to sample collection. After appropriate quality control, we tested different normalization strategies such as normalization with global mean of imputed and unimputed data, with mean of restricted set of miRNAs, quantile normalization and endogenous control normalization to identify the method that best reduces the technical/experimental variability in the data. We identified best endogenous control candidates with expression pattern closest to the mean miRNA expression in the sample, as well as by assessing their stability using a combination of NormFinder and geNorm, BestKeeper and Delta-Ct algorithms under the Reffinder software. Suitability of the four best endogenous controls was validated in 50 hypertensive African Americans from the same trial with qPCR and by evaluating their stability ranking in that cohort. Among the compared normalization strategies, quantile normalization and global mean normalization performed better than others in terms of reducing the standard deviation of miRNAs across samples in the array-based data. Among the four strongest candidate miRNAs from our selection process (miR-223-3p, 19b, 106a, 126-5p), miR-223-3p and miR-126-5p were consistently expressed with the best stability ranking in the validation cohort. Further, the combination of miR-223-3p and 126-5p showed better stability ranking compared to single miRNAs. Overall, we identified quantile normalization followed by global mean normalization to be the best methods in reducing the variance in the data. We identified the combination of miR-223-3p and 126-5p as potential endogenous control in studies of hypertension.